Role of language exposure in early foreign-language learning - Lopriore, L. (Array, 2011)
This paper looks into aural comprehension and oral production of a sample of over 90 young EFL learners from Croatia and Italy who participated in the ELLiE (Early Language Learning in Europe) Project. ELLiE is a European transnational longitudinal study that was carried out in the past four years (2006- 2010) in seven country contexts, England, Italy, the Netherlands, Poland, Spain, Sweden and Croatia. The aim was to investigate what can realistically be achieved in terms of foreign language learning (FLL) in state schools where relatively limited amounts of class time are available for foreign languages. ELLiE has addressed three central issues: the processes of policy implementation, the factors contributing most effectively to the success of early language learning and the linguistic and non-linguistic outcomes. The present contribution draws on findings from the two issues of the project related to factors contributing to FLL success and to learners’ FL outcomes.